Impact of Forest Fires on Soil Degradation – Case of Cork Oak Forest in Algeria - Meghraoui Maamar; Habi Mohamed; Gheffar Mohamed; Chelda Lotfi; Morsli Boutkhil (Ekológia (Bratislava), 2025)
The Mediterranean forest ecosystem has a reputation for being subject to very high fire risks. In Algeria, this ecosystem is seriously threatened and suffers considerable damage every year due to wild and uncontrolled fires. Vegetation and soil are severely affected. The importance of the issues raises the need for a diagnosis of the vulnerability of soils subjected to fire and a reflection on the restoration of the quality of the burnt soils. Being aware of the consequences of the fires, we conducted a study on the impact of fires on the forest cover and, particularly, on the soil. The results showed that soil organic and mineral losses were greater than those of unburned soil, with erosion being 34 times higher. Sloping soils, after fire, degrade more quickly and becomemore vulnerable to erosion and drying out. A high frequency of fires alters the potential of the soil to such an extent that the resilience of the forest and soil could be compromised. The recurrence of fires creates a disturbance of vegetation and ground cover. Forest formations are degraded by fires and gradually replaced by secondary formations; the soil is often eroded. In some places, it has reached the threshold of irreversibility.